Analysis of Individual and Biomechanical Risk Factors Associated with Musculoskeletal Disorders in Online Motorcycle Taxi Drivers - Dani Nasirul Haqi; Endang Dwiyanti; Velu Perumal; Mochamad Haidar; Alifiah Rosydah; Moch Sahri (Health Dynamics, 2025)
Background: Online motorcycle drivers are faced with accidents and occupational health risks when driving, one of which is Musculoskeletal Disorders (MSDs), which can interfere with comfort and focus when driving and can result in accidents. This study aims to analyze individual and biomechanical factors affecting MSDs in online motorcycle taxi drivers. Methods: This is a cross-sectional study with an observational-analytic research design. A questionnaire was used to obtain data on individual and biomechanical factors. The Nordic Body Map (NBM) questionnaire instrument was used to assess MSDs complaints. Results: The most commonly reported slight pain was in the right shoulder (56.7%), waist (55.0%), and upper neck and back (each 53.3%). The majority of online motorcycle drivers (76.7%) experienced low-level complaints. All individual and biomechanical factors have a positive relationship with MSDs complaints in online motorcycle drivers. Conclusions: Drivers must pay attention to their nutritional needs, stop smoking, and stretch 1-2 times a day regularly between work hours.